1988
DOI: 10.1161/01.hyp.11.2.111
|View full text |Cite
|
Sign up to set email alerts
|

Serotoninergic mechanisms in hypertension. Focus on the effects of ketanserin.

Abstract: SUMMARY Aggregating platelets release serotonin, which induces contraction of most vascular smooth muscle by activation of Sj-serotoninergic receptors. Serotonin released in the circulation may contribute to the increase in peripheral resistance of hypertension as the responsiveness of blood vessels from hypertensive animals and humans to the vasoconstrictor action of the monoamine is augmented. The data obtained with the new antihypertensive agent ketanserin may favor that interpretation. Ketanserin is a sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(51 citation statements)
references
References 192 publications
2
48
1
Order By: Relevance
“…7,8 5-HT 2A and 5-HT 2B receptor subtypes belong to the 5-HT 2 family of serotonin receptors and have been implicated in hypertension and other forms of cardiovascular disease such as pulmonary hypertension and atheroschlerosis due to their vasoconstrictive role 9 The 5-HT 2A receptor antagonist ketanserin has an antihypertensive action as the results of most but not all studies have suggested. 7,[10][11][12][13] From these findings we hypothesised that hypertension may be a trait affected by polymorphic variation in the 5-HT 2A receptor gene. A common polymorphism in the 5-HT 2A receptor, the T102C silent mutation exhibits pleiotropic effects and has been associated with a variety of complex disease traits.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 5-HT 2A and 5-HT 2B receptor subtypes belong to the 5-HT 2 family of serotonin receptors and have been implicated in hypertension and other forms of cardiovascular disease such as pulmonary hypertension and atheroschlerosis due to their vasoconstrictive role 9 The 5-HT 2A receptor antagonist ketanserin has an antihypertensive action as the results of most but not all studies have suggested. 7,[10][11][12][13] From these findings we hypothesised that hypertension may be a trait affected by polymorphic variation in the 5-HT 2A receptor gene. A common polymorphism in the 5-HT 2A receptor, the T102C silent mutation exhibits pleiotropic effects and has been associated with a variety of complex disease traits.…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenic effect of 5-HT was initially supported by studies reported decades ago that showed the ability of the 5-HT 2A/2C receptor antagonist ketanserin to reduce blood pressure in the human and in experimental models of hypertension (Nelson et al, 1987;Liu et al, 1991;Azzadin et al, 1995;Krygicz et al, 1996;van Schie et al, 2002), but 380 this effect was later attributed to ␣-adrenergic receptor blockade (Vanhoutte 1991;Wenting et al, 1982;Cohen et al, 1983a;Vanhoutte et al, 1988;van Zwieten et al, 1992). Other 5-HT 2A receptor antagonists such as ritanserin and 6-methyl-1-(1-methylethyl)ergoline-8â -carboxylic acid 2-hydroxy-1-methylpropyl ester (LY53857) have not proven effective in reducing blood pressure (Cohen et al, 1983b;Gradin et al, 1985;Dalton et al, 1986;Nelson et al, 1987;Frishman et al, 1988;Stott et al, 1988;Docherty, 1989), making the effect of 5-HT on blood pressure equivocal.…”
mentioning
confidence: 99%
“…These results may indicate that eperi sone blocks a, and a2 adrenoceptors and serotonin receptors in vascular smooth mus cle. Vascular serotonin (5-HT) receptor sub type is considered to be 5-HT2 (16,17), since ketanserin, a selective 5-HT2 antagonist with some blocking activity, attenuates the se rotonin-induced contractions in dog saphe nous arteries and veins (present study), lowers systemic blood pressure and de creases peripheral vascular resistance (17).…”
Section: Resultsmentioning
confidence: 86%